2005
DOI: 10.1103/physrevb.72.224302
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of hydrogen diffusion by activated hopping and quantum tunneling in ordered intermetallics

Abstract: Diffusion of hydrogen in metals is a fundamental process in hydrogen storage in metal hydrides, hydrogen purification by metal membranes, and in hydrogen embrittlement. Quantitative applications of existing models for hydrogen diffusion by activated hopping and quantum tunneling require large scale first principles calculations that are not well suited to metal alloys containing many structurally distinct interstitial sites. We applied a semiclassically corrected version of harmonic transition state theory in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…This result closely agrees with results of previous calculations [34,35]. We investigated in detail the influence of quantum corrections [2,32,[34][35][36] using the semi-classically corrected transition state theory [37,38] and found that these corrections are relatively small for Ni and do not affect the results presented here. This investigation will be reported elsewhere [39].…”
Section: H In Bulk Nisupporting
confidence: 91%
“…This result closely agrees with results of previous calculations [34,35]. We investigated in detail the influence of quantum corrections [2,32,[34][35][36] using the semi-classically corrected transition state theory [37,38] and found that these corrections are relatively small for Ni and do not affect the results presented here. This investigation will be reported elsewhere [39].…”
Section: H In Bulk Nisupporting
confidence: 91%
“…For instance, previous work has shown that certain NSAs can trap hydrogen in their subsurface [13,28,29]. Beyond the possible hydrogen storage applications of such systems, subsurface and bulk hydrogen has been identified as a reaction intermediate for several catalytic reactions on monometallic catalysts, such as alkene hydrogenation on Pd [30,31] and alkene hydrogenation and methanation on Ni [32][33][34][35]. Additionally, subsurface hydrogen has been shown to affect the binding of other species on single crystals and nanoparticles [36].…”
Section: Introductionmentioning
confidence: 97%
“…Hydrogen diffusion behavior has recently been quantitatively evaluated by electronic state calculations [15][16][17][18][19][20]. In these calculations, hydrogen diffusion is derived from the calculated potential energy.…”
Section: Introductionmentioning
confidence: 99%